Hemogram, fibrinogen concentration and plasma total protein from calves of criollo lageano breed variety hornless and Aberdeen angus breed (Red Angus) on the first six months of life - Schade J.* (2018)
© 2018 Universidade Federal do Rio Grande do Sul. All rights reserved.Background: Neonatal period in bovine presents important variations in hematologic and immunologic parameters, and the resulting mortality rates may be due to increased susceptibility to disease. Race, age, environmental, climate and management factors are sources of CBC's parameters variation in cattle. The objective of this study is to evaluate and compare the CBC variables and concentrations of total protein (PTP) and plasma fibrinogen calves of Criolo Lageano Breed variety hornless and Aberdeen Angus (Red Angus) in the first six months of life, which are produced under extensive management at the Planalto Serrano Catarinense (southern Brazil). Materials, Methods & Results: Two groups were selected, comprising 11 calves of Hornless Criolo Lageano and 14 calves of the Aberdeen Angus breed (Red Angus). Blood samples were collected for complete blood count and determination of total protein concentrations, and plasma fibrinogen in the periods between 24 h and 36, 15, 30, 60, 90, 120, 150 and 180 days of life. The statistical analysis was performed using analysis of variance for repeated measures (ANOVA) and Tukey's test (P < 0.05). During the experimental period infestations by ticks in both races were observed. In the first month of life, blood smears revealed the presence of blood parasites of the genus Babesia spp. and Anaplasma sp. The fluctuations seen for erythrocyte in the neonatal period (30 days), although not significant, consisted of raising the number of values of erythrocytes, hemoglobin (Hb) and packed cell volume (PCV), and reduction in mean corpuscular volume values (MCV). From 90 days of age there was a significant reduction in number of red blood cells and VG values, and elevated MCV values and mean corpuscular volume (MCHC) for the Aberdeen Angus (Red Angus). For the WBC, the neonatal period was marked by increase in the number of lymphocytes and decrease in neutrophil ratio: lymphocyte (N, L) with respect to the inversion of 15 days. In the age group 90 days of life was evident increase in the number of leukocytes and lymphocytes in both races. The plasma fibrinogen concentrations showed no significant variations during the trial period. The plasma total protein (PTP), had higher values on the second day of life, with reductions up to 60 days and gradual increase in subsequent times. Discussion: The fluctuations related to the values of erythrocyte variables in the neonatal period are consistent with results reported by other authors in calves of other races. Changes in erythrocyte values observed from 90 days of age on race Aberdeen Angus (Red Angus) can be attributed to infection by blood parasites and consequent hemolysis. As for the leucocyte count, increasing the number of lymphocytes and inversion of N:L is the neonatal period in a physiological variation and confirms observations made by other authors in calves of other races. In the age group 90 days, leukocytosis by lymphocytosis was related to natural premonition against Babesia spp. and Anaplasma spp., which is documented in cattle in tropical and subtropical regions. When analyzing the PTP values on the second day of life, it can be said that there has been proper transfer of passive immunity in both races, given the high correlation of PTP values and gamma globulins. The reduction of PTP and subsequent elevation values are characteristic of the physiological curve related to degradation of passively transferred immunoglobulin and immunoglobulin synthesis by competent immune system.